Quality of life study of patients with unresectable locally advanced or metastatic pancreatic adenocarcinoma treated with gemcitabine plus nab-paclitaxel versus gemcitabine alone: AX-PANC-SY001, a randomized phase-2 study - DANE, FAYSAL (BMC, 2020)
BackgroundCombination of gemcitabine and nab-paclitaxel has superior clinical efficacy than gemcitabine alone. Nevertheless, health-related quality of life. (QoL) associated with this combination therapy when administered at first-line in advanced pancreatic adenocarcinoma is unknown.MethodsA total of 125 patients were randomized to combination therapy (1000mg/m2 gemcitabine +125mg/m2 nab-paclitaxel) and single-agent gemcitabine (1000mg/m2) arms to take treatment weekly for 7 of 8weeks, and following 3 of 4weeks, until progression or severe toxicity. Primary endpoints were three-months of definitive deterioration free percent of patients, and QoL.ResultsOverall QoL analyses showed that 34 and 58.3% of cases in gemcitabine and gemcitabine+nab-P arms had no deterioration in 3rd month QoL scores (p=0.018). These proportions were 27.3 and 36.6% in 6(th) month assessments, respectively (p=0.357). Median overall survivals in combination and single-agent arms were 9.92months and 5.95months, respectively (HR: 0.64, 95% CI: 0.42-0.86, p=0.038). Median progression free survivals in these treatment arms were 6.28 and 3.22months, respectively (HR: 0.58, 95% CI: 0.39-0.87, p=0.008). Median time-to-deterioration were 5.36 vs 3.68months, and objective response rates were 37.1% vs 23.7% (p=0.009), respectively in combination and single-agent arms.ConclusionsCombination therapy with gemcitabine + nab-paclitaxel had better overall and progression-free survival than gemcitabine alone. Also, combination therapy showed increased response rate without toxicity or deteriorated QoL. Combination treatment with gemcitabine and nab-paclitaxel may provide significant benefit for advanced pancreatic cancer.Trial registrationThis study has been registered in ClinicalTrials.gov as NCT03807999 on January 8, 2019 (retrospectively registered).
Keywords: Nab-paclitaxel; Gemcitabine; Pancreatic cancer; Metastatic; Quality of life; CANCER; FOLFIRINOX; TRIAL